Distribution and invasiveness of Xanthium species in the territory of Bosnia and Herzegovina: Abstract - Kelečević, Biljana; Petković, Vladimir; Mitrić, Siniša; Vrbničanin, Sava; Kovačević, Zlatan (Acta herbologica, 2021)
This is Abstract. Xanthium species are native to America, although it has been a reintroduction between the Old and New worlds. Thanks to selective colonization of genotypes subset they are adapted to different habitats and successfully colonized a large number of countries. Although Xanthium species can use for medical purpose, extracts of X. strumarium have been used for cancer treatment because it inhibits the development of cancer cells and also used for treatment inflammatory diseases, due to its toxicity (high amount of carboxyatractyloside) and wide distribution in agriculture and coastal areas, in most countries they are characterize as invasive weed species. These species invade crops as maize, wheat, soybean, potato, sunflower, tomatoes, tobacco, rape, orchards and vineyard. Nomenclature and determination of plant material was done using modern systematic principles according to Kiraly (2009) and The Plant List (2019). The distribution of the identified species is presented on the UTM (Universal Transverse Mercator) map. The distribution of the determined species was presented on the digital elevation model (Digital Elevation Model, DEM) of BiH with a resolution of 20´20 m in a network of 10´10 km. Quantitative representation of Xanthium species was made by modified Braun Blanquet (1965) model. This work represents detailed research distribution of Xanthium species on the territory of Bosnia and Herzegovina (B&H). On the research area, by morphological determination two species X. spinosum and X. orientale were determined. Within species X. orientale were identified two subspecies X. orientale L. subsp. italicum (Moretti) Greuter and X. orientale L. subsp. riparium (Čelak.) Greuter. The species of the Xanthium genus are widespread on the territory of B&H and occupay new habitats. Based on the results of the distribution and number of identified species, it can be concluded that in the investigated area X. orientale subsp. italicum has an invasive character. Even though X. orientale subsp. riparium was found only in one location, due to the occurrence of cross-polination between subspecies and even species, it can be stated that the species X. orientale has an invasive character. Considering that presence of X. spinosum was ascertained only on the southern parts of B&H, it can be characterized as a harmful weed species which is not in expansion.